1984
DOI: 10.1002/jmv.1890140409
|View full text |Cite
|
Sign up to set email alerts
|

The effects of human cytomegalovirus challenge in vitro on subpopulations of T cells from seronegative donors

Abstract: Purified T cells from seronegative donors were challenged with human cytomegalovirus (CMV) and assayed for response to the mitogen phytohemagglutinin (PHA) administered at various times after virus challenge. Cells were hyporesponsive to PHA added up to 6 h postinfection, while cells challenged with ultraviolet (UV)-inactivated CMV showed normal PHA responses. T-cell populations showed a complete inversion of helper/suppressor ratios by 6 h of infection, as determined by indirect immunofluorescence using the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Decrease of T-cell proliferative response to mitogens, as well as decreased ability to produce pro-inflammatory cytokines, was first described in immune-competent individuals with HCMV mononucleosis. 7,8 The effect could be observed as soon as 6 h after exposure 24 and declined with convalescence. 7 Although experimental data suggested the role of a humoral factor produced by the virus, 24 this could not be identified for many years until the recent discovery by Kotenko et al 9 , who demonstrated that human HCMV encodes a homologue of IL-10.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Decrease of T-cell proliferative response to mitogens, as well as decreased ability to produce pro-inflammatory cytokines, was first described in immune-competent individuals with HCMV mononucleosis. 7,8 The effect could be observed as soon as 6 h after exposure 24 and declined with convalescence. 7 Although experimental data suggested the role of a humoral factor produced by the virus, 24 this could not be identified for many years until the recent discovery by Kotenko et al 9 , who demonstrated that human HCMV encodes a homologue of IL-10.…”
Section: Discussionmentioning
confidence: 96%
“…7,8 The effect could be observed as soon as 6 h after exposure 24 and declined with convalescence. 7 Although experimental data suggested the role of a humoral factor produced by the virus, 24 this could not be identified for many years until the recent discovery by Kotenko et al 9 , who demonstrated that human HCMV encodes a homologue of IL-10. Despite only 27% identity with human IL-10, this virus-encoded protein has high affinity for human IL-10 receptor 1.…”
Section: Discussionmentioning
confidence: 96%
“…Interleukin II was added on day 6, and cultures were tested for cytotoxicity on day 12. b See Table 1, footnote b. HCMV-induced suppression is specific to HCMV CTLs or affects other viral CTL responses as well. However, in other experiments it has been shown that HCMV can suppress not only T-cell proliferation to HCMV (R. Schrier, unpublished observations), but also to herpes simplex virus and mitogens (17,23). HCMV can infect lymphocytes and monocytes, but only a fraction (average, 2%; range, 0 to 15%) of the population shows viral nucleic acid or protein (17,23).…”
mentioning
confidence: 94%
“…However, in other experiments it has been shown that HCMV can suppress not only T-cell proliferation to HCMV (R. Schrier, unpublished observations), but also to herpes simplex virus and mitogens (17,23). HCMV can infect lymphocytes and monocytes, but only a fraction (average, 2%; range, 0 to 15%) of the population shows viral nucleic acid or protein (17,23). Because of the small numbers of PBM involved, it has been difficult to determine how this fraction mediates suppression and whether these cells are killed by the virus.…”
mentioning
confidence: 94%
“…Infection of peripheral blood leukocytes and endothelial cells by CMV results in enhanced production of IL-13, TNF-ot, gamma interferon, and colony-stimulating factor-1 (12,29,49), as well as labile suppressor factor(s) (8,27,45). Finally, infection of bone marrow cells increases both production of alpha interferon, gamma interferon, TNF-ao (7,23,32,33,37,38), and IL-6 and transcription of basic fibroblast growth factor (11,12,22) but transiently suppresses IL-lox and production (48).…”
mentioning
confidence: 99%